Séparer les espaces pour maîtriser le temps - Aurore Flipo; Nathalie Ortar (Temporalités)
Taking a close look at the rhythms and time-uses of coworking spaces, this article means to document how coworkers, being predominantly independent workers and teleworkers, use space to conciliate their personal and professional lives. We show that working in a coworking space is frequently associated with both professional and residential transitions and bifurcations and participate to a broader life projects. Confronted to new temporal and spatial constraints associated with the status of teleworker or independent worker, workers use coworking space to confine work spatially. By offering a separate space dedicated to work, constructing collective rhythms and freeing the domestic space from work, coworking spaces can be used to regulate competing temporalities (individual and social, personal and professional). However, while the literature on coworking has predominantly insisted on its flexible and agile dimension, our study brings out the importance of social and spatial boundaries of activity in the articulation of individual and social temporalities.